WHY TIME MANAGEMENT MATTERS MOST IN TODAY’S FAST-PACED WORLD, ESPECIALLY FOR TEENAGERS - Sevinch Rakhimkulova Azimjonovna (TADQIQOTLAR, 2026)
ANNOTATION: This article explores the growing importance of time management in modern society, focusing particularly on teenagers who face academic pressure, digital distractions, social expectations, and future career planning. It explains why managing time effectively is not just a productivity skill but a life skill that shapes discipline, mental health, success, and personal growth. Without setting clear boundaries and sticking to a well-rounded plan, it is hard to climb the career ladder while simultaneously allocating time meaningfully. Through real-life examples, practical explanations, and research-supported insights, the article demonstrates how mastering time management early can transform teenagers into confident, organized, and goal-oriented individuals.